2013
DOI: 10.1080/19440049.2013.795292
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a confirmatory method for the determination of tranquilisers and a β-blocker in porcine and bovine kidney by LC-MS/MS

Abstract: A method for the confirmation of the tranquilisers azaperone and its metabolite azaperol, of chlorpromazine, propionylpromazine and acepromazine, haloperidol, xylazine and the β-blocker carazolol in porcine and bovine kidney with LC-MS/MS was developed. Various solvents and extraction techniques and different ways of clean-up were tested and verified with incurred pig kidney from an animal study. The best extraction efficiency was reached by extraction with a mixture of ammonia in ethyl acetate and overhead sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Recently, various analytical methods have become available for detecting CRZ, such as high performance liquid chromatography (Fan, Hong, Zhao, Chen, & Wu, 2013;Zhou et al, 2015), gas chromatography-mass spectrometry (Qiu, 2006), liquid chromatography-mass spectrometry (LC-MS) (Bock & Stachel, 2013;Hui, Zhang, Wang, Zhang, & Wang, 2014;Wang et al, 2013;Zhang, Shao, Yin, Wu, & Duan, 2009), ultra-performance liquid chromatography (Cheng, Shen, Zhang, Zhang, & Zhang, 2015), radioimmunoassay methods (Zheng, Zhang, & Feng, 2009), and electrokinetic chromatography (Aranas, Guidote, Haddad, & Quirino, 2011). However, these methods with high sensitivity, high precision, and an ability to simultaneously detect multiple samples require skilled operators and are expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various analytical methods have become available for detecting CRZ, such as high performance liquid chromatography (Fan, Hong, Zhao, Chen, & Wu, 2013;Zhou et al, 2015), gas chromatography-mass spectrometry (Qiu, 2006), liquid chromatography-mass spectrometry (LC-MS) (Bock & Stachel, 2013;Hui, Zhang, Wang, Zhang, & Wang, 2014;Wang et al, 2013;Zhang, Shao, Yin, Wu, & Duan, 2009), ultra-performance liquid chromatography (Cheng, Shen, Zhang, Zhang, & Zhang, 2015), radioimmunoassay methods (Zheng, Zhang, & Feng, 2009), and electrokinetic chromatography (Aranas, Guidote, Haddad, & Quirino, 2011). However, these methods with high sensitivity, high precision, and an ability to simultaneously detect multiple samples require skilled operators and are expensive.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that remifentanil and propofol itself, or combined with other drugs, may cause renal injury in healthy human patients [ 5 10 35 ]. Additionally, all pigs from all groups of our study were premedicated with azaperone, and this drug accumulates in pigs' kidneys and may also contribute to kidney damage [ 3 7 24 38 ]. A significant blood loss followed by volume replacement causes hemodilution.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used extraction methods for this group of compounds are liquid–liquid extraction (LLE), solid-phase extraction (SPE), and QuEChERS (quick, easy, cheap, effective, rugged, and safe). Liquid–liquid extraction is extraction with acetonitrile, methanol, trifluoroacetic acid and ethyl acetate; additionally, ammonia, ammonium formate or acetic acid may be used ( 1 , 4 , 8 , 28 , 29 , 36 , 40 ). A modification of LLE extraction is QuEChERS, in which the sample is additionally purified using octadecylsilane (C 18 ) and primary and secondary amine (PSA) sorbents ( 38 , 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…A more conservative approach granting better purification of the extract but requiring longer sample preparation time is the SPE technique. In this technique, the most commonly used columns are those containing silica, C 18 , and the polymeric reversed-phase sorbent ( 1 , 4 , 22 , 35 , 38 ). The difficulty of determining these substances in kidney tissue prompted some authors to test the possibility of combining the LLE technique with SPE for better purification of the extracts ( 1 , 38 ).…”
Section: Introductionmentioning
confidence: 99%